THERAPIST'S GUIDE TO PRIVATE PRACTICE building a values-based business. - Rees, Sarah ([S.l.] : ROUTLEDGE, 2024)
This book is a comprehensive guide to setting up, running and growing a successful private therapy practice that resonates with your values and professional goals. Guiding you through every detail, from making the initial decision to set up your own private therapy practice to scaling your practice, this guide will support you in overcoming the common challenges you may encounter. It is filled with practical exercises, templates and checklists, including business planning actions at the end of each chapter so you can craft your first business plan. Ensuring you have a solid foundation and can shape a private therapy practice that meets your financial and personal needs while reflecting the passion that led you to your profession. A motivational and inspiring read for therapists, psychotherapists, coaches, and counselors. Get ready to turn your dream into reality and create something profoundly impactful and uniquely yours.
Keywords: Psychotherapy; PSYCHOLOGY / Practice Management; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General